Criminal Accountability for Fraud Committed by Intermediaries in the Civil Servant Recruitment Process in Palangka Raya City - Jhodi Suprianto; Andika Wijaya; Ronaldi (Journal of Law, Politic and Humanities, 2024)
This study examines the efforts of the Palangka Raya Police in preventing and addressing fraudulent practices by intermediaries (brokers) in the Civil Servant (CPNS) recruitment process. The investigation, conducted by the Criminal Investigation Directorate of the Central Kalimantan Police, highlights the critical role of law enforcement in ensuring justice. The study discusses both preventive and repressive measures employed by the police to tackle CPNS fraud. Preventive efforts include educating the public and enhancing supervision of the recruitment process, while repressive measures involve addressing reported fraud cases through a firm legal approach. The study also explores the application of Article 378 of the Indonesian Penal Code (KUHP) in handling CPNS fraud cases, emphasizing the importance of a transparent legal framework and the commitment of law enforcement to effectively combat such crimes. Through this analysis, the study underscores the significance of both legal measures and public awareness in combating fraud and ensuring a fair recruitment process for prospective civil servants.